Comparing the effect of lecture method and cooperative teaching method on the learning, communication skills, and attitudes of students: a quasi-experimental study - Beigzadeh, Amin; Bazyar, Hadi; Delzendeh, Mozhdeh; Razmi, Mohammad Hassan; Sharifi, Nafiseh (Frontiers in Education, 2024)
IntroductionStudents can enhance their understanding of contemporary scientific developments by acquiring proficiency in the English language. Teaching approaches play a crucial role in language acquisition. The objective of this study was to evaluate the effectiveness of the lecture method in comparison to the cooperative learning method, specifically focusing on students’ learning outcomes, communication skills, and attitudes.MethodsThis quasi-experimental interventional study was conducted at Sirjan School of Medical Sciences, Sirjan, Iran in 2023 involving a sample of 30 third-semester students. Participants were randomly assigned to one of two groups, namely the lecture-based teaching group and the cooperative teaching group, with each group consisting of 15 members. Before and after the intervention, questionnaires were completed to assess learning, communication skills, and attitude in both groups. Data were analyzed by independent t-test to compare the two groups. Also, the Levene’s test was used to check the assumption of the equality of variances. Besides, the paired t-test was applied to compare results within each group. The chi-square test was utilized to compare the qualitative variables, while analysis of covariance (ANCOVA) test with adjusting the base value of dependent variables was used to compare the mean differences between the two groups after the intervention.ResultsFindings showed a statistically significant improvement in the mean learning score of the cooperative group after the intervention, compared to the score prior to the intervention (p = 0.007). Moreover, the communication skills and attitude scores of students in both the cooperative and lecture groups showed a statistically significant increase after the intervention, as compared to their pre-intervention scores (p < 0.05). Additionally, following the intervention, the mean scores for communication skills and attitudes were significantly higher in the cooperative group compared to the lecture group, with statistical significance indicated by p < 0.001 and p = 0.03, respectively.ConclusionThis study highlights the effectiveness of cooperative teaching over traditional lecture methods in enhancing students’ learning outcomes, communication skills, and attitudes. The findings indicate that cooperative learning fosters greater engagement, collaboration, and significant interaction among students, ultimately leading to improved academic performance and student satisfaction within the educational framework examined.